(untitled) (Lawrence, 1974)
The book consists of seven papers written as original contributions by prominent agricultural and regional economists, demographers, and administrators. The book also has been carefully edited to provide continuity throughout.
Keywords: Rural development,Phát triển nông thôn; United States